Kriopreservasi untuk Konservasi Plasma Nutfah Tanaman: Peluang Pemanfaatannya di Indonesia - Semuel Leunufna (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
Increasing rate of plant germplasm lost inIndonesia has promoted the implementation of variousmethods for their conservation. Cryopreservation is a techniqueapplicable for a long-term preservation (base collection)of plants possessing non-orthodox (recalcitrant andsemi-recalcitrant) seeds and those propagated vegetatively.The technique can be used as an alternative method fororthodox seed plants preservation in the ex situ conservationsystem. Although field and in vitro collection methods canbe applied for the non-orthodox seed plants, a number ofdisadvantages possesed by these methods, especially in thetropics or the developing countries, deny their use for theestablishment of a long-term germplasm collection. Successfulimplementation of the cryopreservation technique issupported by the development of protocols, which are ableto provide a high recovery rate for species understudy, usingvitrification based methods which are simple, economical,applicable to complex organs, and able to implement a highnumber of explants per experiment. The availability of infrastructuresincluding in vitro culture laboratories, continuesupply of liquid nitrogen is highly supporting the use ofcryopreservation technique in Indonesia.